2011
DOI: 10.1590/s1806-83242011000500015
|View full text |Cite
|
Sign up to set email alerts
|

Halitosis: an overview of epidemiology, etiology and clinical management

Abstract: Halitosis is an unpleasant condition that causes social restraint. Studies worldwide indicate a high prevalence of moderate halitosis, whereas severe cases are restricted to around 5% of the populations. The etiological chain of halitosis relates to the presence of odoriferous substances in exhaled air, especially the volatile sulphur compounds (VSC) produced by bacteria. The organoleptic diagnosis is the gold standard and clinical management includes oral approaches, especially periodontal treatment and oral … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
97
1
35

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 90 publications
(135 citation statements)
references
References 25 publications
2
97
1
35
Order By: Relevance
“…Population-based studies showed variations in prevalence estimates of halitosis, ranging between 6% and 72%. 2,23,24,25 In comparison with other populations, the prevalence observed in this sample may be considered low. However, this prevalence of approximately 22% may have an important impact, considering that the population studied is composed of dental students.…”
Section: Discussioncontrasting
confidence: 61%
See 2 more Smart Citations
“…Population-based studies showed variations in prevalence estimates of halitosis, ranging between 6% and 72%. 2,23,24,25 In comparison with other populations, the prevalence observed in this sample may be considered low. However, this prevalence of approximately 22% may have an important impact, considering that the population studied is composed of dental students.…”
Section: Discussioncontrasting
confidence: 61%
“…23 Pseudo-halitosis is characterized by the absence of clinical determination of halitosis, but there is a clear complaint about it by the individual. 2,28 This should be contextualized in the present study. One limitation of self-reported halitosis is the possible overestimation of the prevalence rates by pseudo-halitosis cases in the sample studied.…”
Section: Discussionmentioning
confidence: 92%
See 1 more Smart Citation
“…Segundo a literatura, 90% dos casos de halitose são atribuídos a causas provenientes da própria cavidade bucal 13 , podendo estar associados a doença periodontal, cárie dentária 1,[5][6][7]10,12,[14][15][16] , processos endodônticos, impactação alimentar, áreas de necrose tecidual 3,10 , presença de corpo estranho no seio maxilar 17 , acúmulo de placa bacteriana, senilidade das glândulas salivares 18 e, principalmente, presença de saburra lingual 3,5,7,10,14,19 .…”
unclassified
“…Em relação à etiologia extraoral ou sistêmica da halitose, podem-se considerar: o diabetes mellitus; as alterações hormonais; o estresse 4,18 ; o tratamento por quimioterapia ou radioterapia 20 ; a bronquite; os problemas renais; a sinusite; a amigdalite; outras doenças otorrinolaringológicas 1,16 ; as disfunções metabólicas; o uso de drogas, e a xerostomia 14,18 . É importante ressaltar que raramente a causa da halitose está relacionada ao trato digestório, o que somente é perceptível em casos de eructação gástrica ou arroto, e refluxo gastroesofágico 3 .…”
unclassified